Empathy levels among dental students and professors from a dental school in the Dominican Republic - Víctor Patricio Díaz-Narváez; María Guadalupe Silva-Vetri; Boni Stocklin; Eugenia González-Díaz; Aracelis Calzadilla-Núñez; Pilar Torres-Martínez; Alejandro Reyes-Reyes (Revista de la Facultad de Medicina)
Introduction: The concept of empathy has been incorporated as one of the key elements for the achievement of the teaching-learning process goals in health science students.